EFEK SUBLETAL FUNGISIDA BERBAHAN DASAR Bacillus amyloliquefaciens PADA BENIH IKAN NILA (Oreochromis niloticus) DAN IKAN MAS (Cyprinus carpio) - Ibnu Bangkit Bioshina Suryadi; Ichsan Nurul Bari; Tamrin Mohamad Lal (Jurnal Akuakultur Rawa Indonesia, 2021)
The use of Bacillus amyloliquefaciens based fungicide has increased along with the modernization of agriculture. On the other hand, freshwater culture is generally juxtaposed with agricultural land. This study was conducted to determine the fungicide's sublethal effect on the survival and haematologist of common carp and tilapia as non-target organisms. The method used was a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments used are: (A) control (0 ppm fungicide), (B) 0.5 ppm fungicide, (C) 1 ppm fungicide, and (D) 10 ppm fungicide. Observation time is 96 hours. Survival, white blood cells, and red blood cells are analyzed using analysis of variance, while the feed response, shock response, and water quality are analyzed descriptively. The results showed that 10 ppm fungicide was not lethal to common carp and tilapia with a survival rate of almost 100%. During 96 hours of fungicide exposure, the average white blood cell (WBC) of common carp increased from 8.84-10.46 x 104 cells/mm3 to 9.56-11.48 x 104 cells/mm3. Meanwhile, the mean WBC of tilapia increased from 11.36-19.44 x 104 cells/mm3 to 20.52-37.38 x 104 cells/mm3. The average red blood cell (RBC) of common carp decreased from 6.60-7.01 x 106 cells/mm3 to 6.06-6.76 x 106 cells/mm3. Meanwhile, the mean RBC of tilapia decreased from 5.26-7.55 x 106 cells/mm3 to 2.21-3.76 x 106 cells/mm3. The results showed that the feed response did not change during the study, but the shock response decreased at 96 hours. Water quality during the study was still in the optimal range for common carp and tilapia culture. Key words : Bacillus amyloliquefaciens, fungicide, sublethal effect, common carp, tilapia